Electrophysiological Correlates of Cue-Related Processing in a Gambling Task: Early Outcome Evaluation or Outcome Expectation? - Zhang, Xiaoyi; Lin, Xiaohong; Takagi, Shiho; Sai, Liyang (Frontiers in Psychology, 2017)
Some recent studies suggest that cues that predict outcomes elicit a negative event-related potential (ERP) component reflecting initial appraisal about whether the desired outcomes are probable or improbable (e.g. reward prediction errors). However, some other studies found those cues that predict outcomes elicited ERPs reflecting an expectation to reward (e.g. reward expectation). Given these mixed findings, the present study aimed to examine whether brain activity elicited by predictive cues in a gambling task reflect reward prediction errors, reward expectation, or both. We employed a gambling task in which participants were told to guess which of two doors hid a reward. At the beginning of each trial, a cue was presented to inform participants the number of doors that hid a reward. We found that predictive cues elicited a feedback-related negativity (FRN)-like negativity at frontal sites around 200-300ms, with cues that fully predict gains or losses larger than cues that predict gains with 50% probability. In addition, predictive cues elicited an expectation-related slow wave, with cues that predict gains with 50% probability larger than cues that fully predict gains or losses. These findings suggest that brain activity not only reflects reward prediction error, but also reflect reward expectation.